(untitled) (LEARNing Landscapes, 2011)
As a poet I am always seeking ecological interconnections amidst body, brain, language, knowing, mind, consciousness, education, imagination, heart, cognition, and spirit. In language play I hope to find my way to a purposeful pedagogy that acknowledges and honours how learning is always a holistic adventure in process and flux, an adventure of human becoming filled with wonder and mystery beyond the counting, but always abundantly available for courting with wild delight and desire.